Care Cascades for Hypertension in Low-Income Settings: A Systematic Review and Meta-Analysis - Demetrio Lamloum; Demetrio Lamloum; Federico Fassio; Brianna Osetinsky; Brianna Osetinsky; Fabrizio Tediosi; Fabrizio Tediosi (Frontiers Media S.A., 2023)
Objective: High blood pressure is the leading risk factor for cardiovascular disease. The hypertension care cascade (HCC) is increasingly being used to evaluate the effectiveness of interventions. This systematic review aims to examine HCC in low-income settings.Methods: The search strategy included articles published between January 2010 and April 2023. We excluded studies with incomplete HCC, on fragile patients or aged <18 years, reviews. We used the MOOSE guideline. Five researchers retrieved data on the survey year, country, population, HCC and diagnostic methods for hypertension. We used JBI Critical Appraisal Tools for quality assessment.Results: Ninety-five articles were analyzed. Average hypertension prevalence was 33% (95% CI: 31%-34%), lower in LICs than in LMICs (25% vs. 34%). The overall mean awareness of hypertension was 48% (95% CI: 45%-51%), its treatment was 35% (95% IC: 32%-38%) and its control 16% (95% CI: 14%-18%). In almost all steps, percentages were lower in LICs and in Sub-Saharan Africa.Conclusion: Trends in HCC vary between countries, with poorer performance in LICs. This review highlights the need for interventions tailored to low-income settings in order to improve hypertension care.